PERBEDAAN KADAR PROTEIN PADA ASI DAN SUSU FORMULA BAYI USIA 0-6 BULAN - Rizki Yuniarti, Hadi Barru Hakam Fajar Siddiq, Siti Nur Azizah (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2019)
Protein is the main nutrient needed at the beginning of life, especially babies, but many things that cause the baby cannot be breastfed by his mother. The alternative is to give cow milk as a substitute for ASI. This study aims to determined the differences in protein levels and what protein levels were found in breast milk and formula cow's milk for children aged 0-6 months in Jember Regency. The kjehdahl method was selected, namely destruction, distillation, and titration to determined protein levels in breast milk and formula milk. From the results of the experiment, it was found that protein levels were 0.28%, 0.36% and 0.17% for formula A, B and ASI milk. The results of the SPSS analysis test using the T test showed a significance value of 0,189 (p0.05). These results indicate that there are no differences in the levels of protein contained in formula milk and breast milk.Keywords: breast milk, formula milk, protein content, kjehdahl method.